Investigation on cyclic variations of a diesel engine operating with alcohols and biodiesel blends - Mohd Hafizil, Mat Yasin (2018)
Butanol and ethanol are second-generation biofuels that have received great attention in recent years. These alcohols obtained from the biomass feedstock sources to improve the fuel properties and performance of the recent fuels. However, there are certain grey aspects in the combustion characteristics of butanol and ethanol blends in various operating speeds and loads using combustion cyclic variation analysis to be further investigated. This previous work investigated the use of commercially available mineral diesel (D), palm biodiesel (B), butanol (10%)-diesel (90%) (DBu10), butanol (10%)-palm biodiesel (90%) (BBu10), ethanol (10%)-diesel (90%) (DE10), and ethanol (10%)-palm biodiesel (90%) (BE10) fuels. The objectives of this study are to characterise the physico-chemical properties, to investigate the effects of loads and speeds, and to analyse the combustion stabilities in cylinder pressure using recurrence plot (RP) and recurrence quantification analysis (RQA) on tested fuels. Experimental works were conducted on a single cylinder, direct injection diesel engine to investigate the cyclic combustion variations of cylinder pressure profiles and peak cylinder pressure, Pmax. The recorded 200 consecutive cycles were recorded to analyse the cyclic combustion variations for each fuel at the different operating condition. Those parameters were statistically analysed to obtain the coefficient of variation (COV) for Pmax. Also, the novel approaches, recurrence plot (RP) and recurrence quantification analysis (RQA) are introduced to evaluate qualitatively and quantitatively the combustion instabilities for each fuel at different speeds and load rates. The results showed that butanol and ethanol blends have comparable averaged cylinder pressure profiles with D and B. Also, higher peak cylinder pressures were observed for butanol and ethanol blends with the increase in engine loads but gradually decreased at 2300 rpm. For all six fuels, most of the peak HRR occurred at 7-10 deg.CA with differences between 8-10%. Regarding cyclic combustion variability, particularly cylinder pressure, higher cylinder pressure cyclic variability occurred at high load and speed for all test fuels, especially DE10 with higher COVPmax values obtained for 200 consecutive cycles. By using RP and RQA, the dynamical characteristics of combustion in diesel engine through Pmax cyclic variations were investigated. For all fuels, most combustion processes in different operating conditions exhibit many chaotic features and deterministic nature that can be easily related to patterns in RPs and RQAs. Thus, in this case, DE10 produced the most chaotic combustion irregularities and higher cyclic variations for the time series in those conditions. In conclusion, cylinder pressure variations in the time series were found to be affected by the fuel composition of butanol and ethanol in the blends and types of fuel in engine operation. Overall, these findings have contributed to the fundamental understanding of the alcohol blends operating with engines and provide further information to achieve the most efficient fuel combustion of engine with advanced fuel injection technologies.